Engaged spirituality : social change and American religion - Stanczak, Gregory C., 1967- (Rutgers University Press, 2006)
While scholars have long recognized the importance that religion and religious organizations have played in social activism, they have typically seen spirituality as a private matter with few practical implications. In Engaged Spirituality, Gregory C. Stanczak challenges this assumption, arguing that spirituality plays an important social role as well. Based on more than one hundred interviews with individuals of diverse faith traditions, the book shows how prayer, meditation, and ritual provide foundations for activism.